Sejarah Kehidupan Nabi Muhammad dan Kemenangan Umat Islam - Muhammad Rais Amin (TASAMUH: Jurnal Studi Islam, 2017)
Prophet Muhammad announced a surprising sense of revolution containing in his speech: “O people, verily your Lord is one and your father is one. Each of human being is from Adam, while Adam comes from the land. Verily the noblest among you is the most pious; there is no difference between Arabs and non-Arab except for piety. “The call of the Qur’an contains two things, the two buffers, the underlying sense of safety and security. Islam on both of these sturdy and stand in every age and in every place, unity in concept to the human. A human being is a human being that another brother of the two reviews, first, that God is one, and secondly, that human ancestors were one. Then, after the Prophet emigrated to Medina and take power, the teachings are passed and are coupled with the teachings of amaliyah or acts, which regulate human life and society according to their safety. Maintaining the security and safety of the people in general, and his followers are still few in number, but got the persecution of enemies. Prophet gained victory after victory. The victory can seize the city of Mecca is the biggest lesson that adds firmly trust the people believe in Allah and surrender to Him